Can monetary valuation undermine nature conservation? Evidence from a decision experiment - Julian Rode; Marc Le Menestrel; Gert Cornelissen (Helmholtz-Zentrum für Umweltforschung (UFZ), 2015)
Nature conservation scientists and practitioners have voiced the concern that a conservation discourse based on economic arguments and monetary valuation may undermine conservation efforts by eroding ("crowding out") the influence of other arguments for nature conservation. This paper presents the results of a decision experiment in which nature conservation is framed using an economic, a non-economic, or a combined discourse before participants take hypothetical decisions on the construction of hydropower dams in the Bolivian Amazon. We find that an economic discourse with monetary valuation framing leads to significantly fewer pro-conservation decisions, that is, decisions against dam construction. This is the case when a cost-benefit analysis inclusive of environmental costs reveals that the dam is economically viable (i.e., there remains a trade-off between economics and conservation), but also when such a costs-benefit analysis indicates that the dam is not viable (i.e., no trade-off). The results suggest that an economic discourse with monetary valuation framing can indeed undermine nature conservation efforts. They also suggest that the effect can be avoided, however, by presenting non-economic arguments side by side with an economic rationale.
Keywords: D61; D63; D81; H41; O13; Q01; Q34; Q51; Q56; Q57; 330; nature conservation; policy discourse; framing; monetary valuation; crowding out